2011
DOI: 10.1007/s12032-011-0063-1
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-9 is consistently expressed in Hodgkin/Reed-Sternberg cells and has no impact on survival in patients with Epstein–Barr virus (EBV)-related and non-related Hodgkin lymphoma in Brazil

Abstract: Clinical and histological features of classical Hodgkin lymphoma (cHL) are primarily due to the effects of cytokines and enzymes produced by Hodgkin/Reed-Sternberg (HRS) cells and their surrounding inflammatory cells. In EBV-related cancers, the expression of viral latent membrane protein 1 correlates with an increased MMP9 expression. In this study, we evaluated the prognostic relevance of MMP9 expression and EBV status in HRS cells in patients with cHL in Brazil. We selected 97 patients with cHL for EBV and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…The expression of MMP9 has been associated with increased aggressiveness and poor prognosis in patients with non-Hodgkin lymphoma [10], but an influence on prognosis has not been reported in the few studies on cHL [11][13]. Flavell et al [11] reported that the survival analysis performed on their cases was compromised by the fact that there were a small number of patients in the MMP9-positive group, although there was a tendency toward an adverse outcome in this category.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The expression of MMP9 has been associated with increased aggressiveness and poor prognosis in patients with non-Hodgkin lymphoma [10], but an influence on prognosis has not been reported in the few studies on cHL [11][13]. Flavell et al [11] reported that the survival analysis performed on their cases was compromised by the fact that there were a small number of patients in the MMP9-positive group, although there was a tendency toward an adverse outcome in this category.…”
Section: Discussionmentioning
confidence: 99%
“…The MMP9 antibody used in our study was the same used by Souza et al [13] in their study with 97 Brazilian patients, although the dilution was different (1∶100 versus 1∶200). Additionally, differences in immunohistochemical staining evaluation and the use of TMA in our study might have accounted for the discrepant results regarding the prognostic relevance of MMP9.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations